Predicting delamination in multilayered CFRP laminates accounting for different failure modes. Issue 1 (21st October 2015) - Simon, Jaan‐Willem; Höwer, Daniel; Reese, Stefanie
Abstract: Carbon fiber reinforced plastics (CFRP) are mostly used in multilayered laminates, which consist of several very thin layers stacked over each other. For such laminated structures, delamination represents one of the most critical states of failure. In order to predict both the onset as well as the propagation of delamination, a cohesive zone‐like continuum damage model is proposed in this paper. This damage model is directly incorporated into a solid‐shell finite element with finite thickness. Further, the formulation is capable of considering the interaction of different failure modes. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)